A30. Pulmonary Vices : Cigarette Smoke, Alcohol and Oxidative Stress Responses of the Lung 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a1263
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptors Are Sensors For Ethanol In Lung Fibroblasts

Abstract: Background-Chronic ethanol abuse in humans is known to independently increase the incidence of and mortality due to acute lung injury in at-risk individuals. However, the mechanisms by which ethanol affects lung cells remain incompletely elucidated. In earlier work, we reported that ethanol increased the expression in lung fibroblasts of fibronectin, a matrix glycoprotein implicated in lung injury and repair. This effect was blocked by α-bungarotoxin, a neurotoxin that binds certain nicotinic acetylcholine rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that ARDS occurs 3.7 times more frequently in people meeting the diagnostic criteria for alcohol-use disorders (Moss, Bucher, Moore, Moore, & Parsons, 1996; Ritzenthaler, Roser-Page, Guidot, & Roman, 2013). Excessive alcohol exposure can damage target organs via mechanisms including inflammation, oxidative stress, and/or tissue remodeling.…”
Section: Alcohol and The Lungmentioning
confidence: 99%
“…Previous studies have demonstrated that ARDS occurs 3.7 times more frequently in people meeting the diagnostic criteria for alcohol-use disorders (Moss, Bucher, Moore, Moore, & Parsons, 1996; Ritzenthaler, Roser-Page, Guidot, & Roman, 2013). Excessive alcohol exposure can damage target organs via mechanisms including inflammation, oxidative stress, and/or tissue remodeling.…”
Section: Alcohol and The Lungmentioning
confidence: 99%
“…Previously, we showed that α4 nicotinic acetylcholine receptors (α4 nAChRs) act as alcohol sensors in mouse lung fibroblasts. Both pharmacological inhibitors and down‐regulation of α4 nAChR by siRNA inhibited the alcohol‐induced expression of fibronectin in these cells (Ritzenthaler et al, 2013; Roman et al, 2005). These nAChRs are members of a family of nonselective cation channels that are activated by the neurotransmitter acetylcholine and are widely expressed at synaptic junctions (Lindstrom, 1997; Lindstrom et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A further area of focus would be to determine the effect of oxidative stress on nicotinic acetylcholine receptor activation. We have published findings that a modification of two cysteines in the α4 subunit within the α4 nAChR inhibits alcohol-induced cellular modifications [85]. Anti-oxidants and oxidants, N-acetylcysteine, paraquat, H 2 O 2 , and nicotine will be used on cells in vitro with modified cysteine "knock ins" being developed for the α subunits in the α7 nAChR to test possible activation mechanisms.…”
Section: α7 Nachr Activation By Oxidative Stressmentioning
confidence: 99%